2021
DOI: 10.1371/journal.pone.0259444
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of the different relaxation periods during passive intermittent static stretching on arterial stiffness

Abstract: To clarify whether the relaxation period during stretching affects the degree of elevated shear rate and the degree of reduction of arterial stiffness, we examined relaxation duration to build an adequate stretching protocol. In Experiment 1, the changes in cardiac output, the shear rate in the posterior tibial artery, and blood volume in the calf muscle were measured during recovery (0–60 s) from a single bout of one-legged passive calf stretching in 12 healthy young men. In Experiment 2, the effects of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Acute stretching of a local body part is well known to elicit an increase in arterial compliance and a reduction in arterial stiffness in that body part ( Yamato et al, 2017 ; Higaki et al, 2021 ; Ikebe et al, 2022b ). Our results are consistent with those of previous studies and indicate that acute cervical stretching increased carotid arterial distensibility without reducing systemic arterial stiffness (haPWV and CAVI).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute stretching of a local body part is well known to elicit an increase in arterial compliance and a reduction in arterial stiffness in that body part ( Yamato et al, 2017 ; Higaki et al, 2021 ; Ikebe et al, 2022b ). Our results are consistent with those of previous studies and indicate that acute cervical stretching increased carotid arterial distensibility without reducing systemic arterial stiffness (haPWV and CAVI).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the findings of animal studies indicate that arterial structural changes (i.e., in the composition of elastin and collagen) are less likely to occur in a relatively short period (Tanaka et al, 2000;Nosaka et al, 2003;Maeda et al, 2005). Second, in terms of arterial functional factors, previous studies have reported that stretching induces blood flow and shear rate during the relaxation period (Yamato et al, 2021), and that this stimulus can cause a reduction in arterial stiffness (i.e., an increase in arterial compliance) after stretching (Hotta et al, 2013;Higaki et al, 2021;Yamato et al, 2021;Hotta et al, 2018). In our experimental data, an increasing tendency of shear stress immediately after cervical stretching was observed (CON vs. CS: 1.4 ± 5.9% vs. 10.7 ± 5.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the degree of reduction in arterial stiffness, continuous high shear stress (e.g., shear rate) on endothelial cells induces vasodilation with increased secretion of endothelial-derived relaxation factor [ 20 - 24 ]. We, as well as others, have demonstrated that acute passive static stretching of the quadriceps or calf muscle increased blood flow and shear rate in the stretched leg [ 15 , 16 , 25 - 27 ]. Conversely, the blood flow and shear rate in the non-stretched leg did not change [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We, as well as others, have demonstrated that acute passive static stretching of the quadriceps or calf muscle increased blood flow and shear rate in the stretched leg [ 15 , 16 , 25 - 27 ]. Conversely, the blood flow and shear rate in the non-stretched leg did not change [ 15 , 25 ]. Therefore, these findings suggest that habitual repetition of the increase in shear rate induced by stretching of the lower limb may result in reduced arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%